Contradiction-oriented problem solving for innovations: five opportunities for China's companies - Runhua Tan (Journal of Innovation and Entrepreneurship, 2015)
This paper focuses on the importance of contradictions and solving them for improving the innovative capabilities of engineers and their companies in China. The data are analyzed based on the collections from ten classes and ten projects of engineers from a national training program. A pattern that is an additional process model from main innovation processes is set up. Five innovative opportunities for companies are extracted. The study shows that to find and solve contradictions are the driving forces indeed for increasing both the engineers' and companies' innovative capabilities now in China.
Keywords: 650; Contradiction solving; Training engineer; TRIZ; Innovative capability; Five opportunities